"I am Coach": A Model for Developing Students as Their Own Best Coach. Issue 7 (1st September 2016) - Mowling, Claire M.; Martin, Ellen H.
Abstract : The purpose of this article is to describe a hybrid model designed to assist in developing students as their own best individual and peer coaches. As students interact with the content through a hands-on approach, they are able to develop higher-order thinking skills by analyzing and evaluating skill performance using a games-centered approach. Participation in the process of skill analysis and evaluation may lead to a deeper understanding of skill execution and the ability to make appropriate changes to personal performance and create more constructive practice sessions.